2018
DOI: 10.1159/000489580
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid for IgA Nephropathy: Are They Really Therapeutic?

Abstract: Background: IgA nephropathy (IgAN) is a common chronic glomerular disease that, in most patients, slowly progresses to end-stage kidney disease. The therapy with corticosteroid in IgAN is still a worldwide problem that is confusing the clinicians. Methods: MEDLINE, EMBASE, the Cochrane Library, and article reference lists were searched for randomized controlled trials (RCTs) that compared corticosteroids with placebo and any other non-immunosuppressive agents in treating IgAN. Twelve RCTs involving 1,057 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…IgA nephropathy (IgAN) is the most common primary glomerulonephritis that is used worldwide, especially in Asian countries [1, 2]. Approximately 20–30% of the patients with IgAN will progress to end-stage renal disease within 20 years [3, 4]. However, the diagnosis of IgAN requires a renal biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is the most common primary glomerulonephritis that is used worldwide, especially in Asian countries [1, 2]. Approximately 20–30% of the patients with IgAN will progress to end-stage renal disease within 20 years [3, 4]. However, the diagnosis of IgAN requires a renal biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the Pozzi protocol can significantly reduce proteinuria and protect against renal function deterioration in IgAN patients [10,11]. However, the outcomes of glucocorticoid therapy for IgAN remain inconclusive and conflicting [17]. In recent years, large randomized controlled trials (RCTs) on corticosteroid therapy for IgAN patients, such as the STOP trial [18] and the TESTING trial [19], included patients with primary IgAN proteinuria (1.0-3.5 g/24 h) and glomerular filtration rate (eGFR) 20-120 ml/min/1.73m 2 for corticosteroid therapy (0.6-1.0 mg /Kg/d), and the results show that the corticosteroid therapy is beneficial to the alleviation of proteinuria and the protection of the renal function of IgAN patients in the short term, but the server adverse effects of corticosteroid therapy are also noticed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the Pozzi protocol can signi cantly reduce proteinuria and protect against renal function deterioration in IgAN patients [10,11]. However, the outcomes of glucocorticoid therapy for IgAN remain inconclusive and con icting [17]. In recent years, large randomized controlled trials (RCTs) on corticosteroid therapy for IgAN patients, such as the STOP trial[18] and the TESTING trial [19], included patients with primary IgAN proteinuria (1.0-3.5g/24h) and glomerular ltration rate (eGFR) 20-120ml/min/1.73m 2 for corticosteroid therapy (0.6-1.0mg /Kg/d), and the results show that the corticosteroid therapy is bene cial to the alleviation of proteinuria and the protection of the renal function of IgAN patients in the short term, but the server adverse effects of corticosteroid therapy are also noticed.…”
Section: Discussionmentioning
confidence: 99%